Airway Epithelial Inflammation In Vitro Augments the Rescue of Mutant CFTR by Current CFTR Modulator Therapies - Gentzsch, Martina; Cholon, Deborah M.; Quinney, Nancy L.; Martino, Mary E. B.; Minges, John T.; Boyles, Susan E.; Guhr Lee, Tara N.; Esther, Charles R.; Ribeiro, Carla M. P. (Frontiers in Pharmacology, 2021)
In cystic fibrosis (CF), defective biogenesis and activity of the cystic fibrosis transmembrane conductance regulator (CFTR) leads to airway dehydration and impaired mucociliary clearance, resulting in chronic airway infection and inflammation. The most common CFTR mutation, F508del, results in a processing defect in which the protein is retained in the endoplasmic reticulum and does not reach the apical surface. CFTR corrector compounds address this processing defect to promote mutant CFTR transfer to the apical membrane. When coupled with potentiators to increase CFTR channel activity, these drugs yield significant clinical benefits in CF patients carrying the F508del mutation. However, processing of CFTR and other proteins can be influenced by environmental factors such as inflammation, and the impact of airway inflammation on pharmacological activity of CFTR correctors is not established. The present study evaluated CFTR-rescuing therapies in inflamed CF airway epithelial cultures, utilizing models that mimic the inflammatory environment of CF airways. Primary bronchial epithelial cultures from F508del/F508del CF patients were inflamed by mucosal exposure to one of two inflammatory stimuli: 1) supernatant from mucopurulent material from CF airways with advanced lung disease, or 2) bronchoalveolar lavage fluid from pediatric CF patients. Cultures inflamed with either stimulus exhibited augmented F508del responses following therapy with correctors VX-809 or VX-661, and overcame the detrimental effects of chronic exposure to the CFTR potentiator VX-770. Remarkably, even the improved CFTR rescue responses resulting from a clinically effective triple therapy (VX-659/VX-661/VX-770) were enhanced by epithelial inflammation. Thus, the airway inflammatory milieu from late- and early-stage CF lung disease improves the efficacy of CFTR modulators, regardless of the combination therapy used. Our findings suggest that pre-clinical evaluation of CFTR corrector therapies should be performed under conditions mimicking the native inflammatory status of CF airways, and altering the inflammatory status of CF airways may change the efficacy of CFTR modulator therapies.